METHOD OF DECODING BINARY SEQUENCES, INVARIANT TO STATISTICAL - Yudin, O. K.; Kurin, K. O. (Science-based technologies, 2013)
Development of compression methods based on principles of information redundancy elimination which are essentially different from statistical – methods of structural coding — is considered actual. The rule about unambiguity of representation of binary sequence by serial number of invariant coding is described and proved. According to this rule it is possible to create only one serial number of invariant coding at set values of structural signs for binary sequence and, on the contrary, only one binary sequence can be restored by the value of serial number of invariant coding at the set restrictions on value of structural signs. The rule about restoration of binary sequence by invariant decoding according to which the initial sequence can be restored without any curvatures based on values of serial number of invariant coding and structural signs — quantity of bit transitions and quantity of ‘1’ elements in binary sequence, is described and proved. The analytical structural scheme of the offered method of invariant decoding is created.